Design and evaluation of oil well cement-based composite materials improved by multi-component flexible materials - Hui Zhang; Chengwen Wang (Materials Research Express)
Complex oil and gas wells often experience complex stresses underground during the extraction process, which can easily cause damage to the cement paste. To improve the flexibility of oil well cement-based composite materials for wells, the evaluation was conducted on the effects of polyethylene fibers, elastic particles, and epoxy resin in cement slurry. Three types of flexible materials were used to design improved flexible cement-based composite materials for wells, and the performances of cement paste were evaluated. The results show that polyethylene fibers have excellent properties. With appropriate dosage, the flexural strength of oil well cement paste can be improved through bonding and traction, and there is no negative effect on the rheology of cement slurry. Elastic particles and epoxy resin can enhance the deformability and flexibility of cement paste by forming flexible structural centers and polymer film structures. The cement slurry established using polyethylene fibers, elastic particles, and epoxy resin has excellent workability, higher mechanical properties, lower elastic modulus, and better flexibility compared to conventional cement slurry systems. Compared with the conventional cement slurry system, the compressive strength and flexural strength of the flexible oil well cement-based composite materials cured for 24 h increased by 12.44% and 26.03% respectively, while the triaxial elastic modulus decreased by 33.68%. Different flexible materials form a synergistic effect by filling the interior of cement paste to improve its flexibility.